The effect of guided imagination strategy using Google Classroom on achievement and imaginative thinking skills of biology among scientific fourth graders (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify (the effect of the guided imagery strategy using Google Classroom on the imaginative thinking skills of biology among fourth-grade students of science) the researcher adopted the partial-controlled experimental design to achieve the goal of the research, and the current research is limited to fourth-grade students in science and in secondary schools the official affiliate of the Ministry of Education, Third Rusafa, in Baghdad Governorate for the academic year (2021-2020) and Zahrat Al-Rabea High School for Girls was chosen to be its students as the research sample intentionally. Then four halls were chosen from a total of 17 halls to organize two divisions of students of the fourth grade of science, one experimental and the other controlling, as the research sample reached (68) students, of (34) female students in the experimental group and (34) female students in the control group, the researcher was rewarded with the two research groups in the variables (IQ test, chronological age, biology subject scores in the third grade final test, previous bioinformatics test, imaginative thinking skills test), and the scientific subject was defined in the following chapters (classification of living organisms, ecology and ecosystem science, The food chain and the cycle of elements in nature, factors affecting the environment, the adaptation of animals to the environment) from the book on biology to be taught for the academic year (2021-2020) AD, the behavioral objectives of these classes were formulated and amounted to (150) behavioral objectives similar to the six levels of Bloom's classification in the cognitive domain (remember, comprehend, apply, analyze, synthesize, evaluate) according to the proposed lessons for each semester, and then the teaching plans were prepared for the two groups, as The researcher taught the two research groups by herself during the period of the experiment that lasted (10) weeks of the second semester of the academic year (2021-2020), As for the research tools, the researcher prepared a test for imaginative thinking skills consisting of (13) questions, and the validity of the tool was verified by presenting it to a group of arbitrators, and it was applied to the two survey samples, one of them to know the time of the answer and the extent of clarity of the paragraphs and the other one is for the purpose of analyzing the test items statistically to extract the effectiveness of the wrong alternatives, the difficulty factor, the ease and distinction coefficient, and extract the stability for the two tests.